2014
DOI: 10.1002/bmc.3360
|View full text |Cite
|
Sign up to set email alerts
|

Use of specific polysaccharide‐immobilized monodisperse poly(glycidyl methacrylate) core–silica shell microspheres for affinity purification of lectins

Abstract: Immobilization of polysaccharides (yeast mannan and gum arabic) on the macroporous poly(glycidyl methacrylate) monodisperse microspheres coated with silica (SiO2 )-containing amino groups on the surface was used to prepare affinity sorbents for lectin purification. The efficiency of isolating mannose specific Pisum sativum lectin was demonstrated on sorbent with immobilized yeast mannan and that of galactose specific Glycine hispida lectin on sorbent with immobilized gum arabic. The microspheres with immobiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In parallel to our results, Antonyuk et al developed specific polysaccharide-immobilized monodisperse poly(glycidyl methacrylate) core-silica shell microspheres and they achieved to immobilize 50 mg of polysaccharide (yeast mannan and gum arabic) per 1 g of the matrix, which is 10 times higher than the capacity of epoxy-activated Sepharose 6B (agarose gel matrix). This study is important in order to show interaction and affinity between polysaccharides and lectins [26]. Another study, Locke et al reported that PEGylated ConA were potential improving of a ConA-based long term continuous glucose monitoring device for in vivo applications [6].…”
Section: Temperature Effectmentioning
confidence: 99%
“…In parallel to our results, Antonyuk et al developed specific polysaccharide-immobilized monodisperse poly(glycidyl methacrylate) core-silica shell microspheres and they achieved to immobilize 50 mg of polysaccharide (yeast mannan and gum arabic) per 1 g of the matrix, which is 10 times higher than the capacity of epoxy-activated Sepharose 6B (agarose gel matrix). This study is important in order to show interaction and affinity between polysaccharides and lectins [26]. Another study, Locke et al reported that PEGylated ConA were potential improving of a ConA-based long term continuous glucose monitoring device for in vivo applications [6].…”
Section: Temperature Effectmentioning
confidence: 99%
“…A strategy that would allow a fast uptake and controlled release of halogen-containing compounds at low cost independent of time and place should be highly attractive for applications that include water treatment and medical technologies. With this objective in mind, we focused on the use of the polymer microspheres, as these exhibit a large specific surface area, fast response, the potential to be used in mass production, high diffusibility, and ease of recovery and handling. Using solid microspheres that consist of hydrophobic polymers has led to the development of selective and fast separation methods for metal ions and biomolecules. However, the dispersion stability of these microspheres, which is usually granted by the electrostatic repulsion, may be decreased upon adsorption of the target molecules on the microsphere surfaces, resulting in a decreased specific surface area and reusability due to the aggregation . Moreover, hydrogel microspheres (microgels), which have a three-dimensional cross-linked structure that swells in water, permit the controlled uptake/release of functional molecules.…”
Section: Introductionmentioning
confidence: 99%